Implementación de un esquema de seguridad perimetral de vigilancia y monitoreo de video en tiempo real aplicando la tecnología cctv, mediante cámaras de seguridad analógicas para los laboratorios y talleres de las carreras de ingenierías: electromecánica, eléctrica, industrial, mantenimiento de redes y software de la unidad de ciencias de la ingeniería y aplicadas en la Universidad Técnica de Cotopaxi - Basantes Chugchilan, Olber Lenin (2015)
For appease to the growing measure of delinquency the humanity have the necessity of to cause their investments in methods of protection for combat and to control in the possible the actuate of persons unscrupulous that attempt commit acts illicit against your ownership. The employ of systems of electronics security intervening cameras of security analogues and cameras ip are in the present time a method of technology predominate in the industry of surveillance and monitoring so much in atmospheres interiors how externals, precisely is how the CCTV (Closed Circuit Television) is designed for realize tasks of supervision and control audiovisual to distance checking of manner centralized the activities that realize inside of the perimeters that preserve every an of the cameras of surveillance that form the system of security. Every one of the components that integrate the system of security have that be necessarily interconnected intervening an connection of point to point forming a circuit how such for the sending and reception of the pictures captured by the cameras of security, moreover the system have that be accompanied the search and storage of the events that the system monitors for count with evidences that later will be analyzed for the taking of decisions respects. The execution the system of edge security of surveillance and monitoring of video in real time, using cameras of analogues security installed in the interior of the laboratories and workshops of electromechanical, electrical, industrial, networks and software fulfilled with the objectives proposed analyzing the competents requeriments and apts that gain the visualization in real time of the atmospheres and the differents activities that develop in every dependence.